-24-7n=-8(3-6n)

Simple and best practice solution for -24-7n=-8(3-6n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -24-7n=-8(3-6n) equation:


Simplifying
-24 + -7n = -8(3 + -6n)
-24 + -7n = (3 * -8 + -6n * -8)
-24 + -7n = (-24 + 48n)

Add '24' to each side of the equation.
-24 + 24 + -7n = -24 + 24 + 48n

Combine like terms: -24 + 24 = 0
0 + -7n = -24 + 24 + 48n
-7n = -24 + 24 + 48n

Combine like terms: -24 + 24 = 0
-7n = 0 + 48n
-7n = 48n

Solving
-7n = 48n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-48n' to each side of the equation.
-7n + -48n = 48n + -48n

Combine like terms: -7n + -48n = -55n
-55n = 48n + -48n

Combine like terms: 48n + -48n = 0
-55n = 0

Divide each side by '-55'.
n = 0

Simplifying
n = 0

See similar equations:

| 42=3(2-3n)-6 | | -19=3(7+3n)+8(8n-5) | | 180=111-u | | -12+19/-7= | | -12+-42/-7= | | 60x^2-20x+1=0 | | 84=2w+2L-3 | | 15y-11y=20 | | -12+-126/-7= | | x^2+(x*y)=120 | | 84+3x=1x | | -9u-5+6=19 | | -12+h/7=6 | | -a+5+6a=1+5a+3 | | -12+h/7= | | 8x+4(2-3x)=36-6x | | (4x-3)+3(3x+6)=5x-1 | | 4x^3-33x^2-30x=0 | | 2x+17+3x-4=180 | | 32=2x+14 | | 0.625=-0.50x | | 88+1.5h=94+2h | | 85=3(x-1)+8x | | -5(k-1)-(-6k+1)=9 | | 7a^2+49a+60=0 | | (sin(x))*2=116 | | 1x+-7=2x+-6 | | (sin(x))2=116 | | 4x^3-33x-30x=0 | | -3(2y-2)-y=-2(y-2) | | 4v-(6v+8)=8v-38 | | 88+1.5h=94-2h |

Equations solver categories